On Kolmogorov-type inequalities for fractional derivatives of functions of two variables - Babenko, V. F.; Pichugov, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We prove a new exact Kolmogorov-type inequality estimating the norm of a mixed fractional-order derivative (in Marchaud's sense) of a function of two variables via the norm of the function and the norms of its partial derivatives of the first order.